The investigation of chemical vapor deposited copper-based niobium films. (16th April 2021) - Li, Min; Pu, Guo; Luo, Yuchuan; Ye, Zongbiao; Wei, Jianjun; Chen, Shuwei; Wu, Andong; Yang, Li; Zhang, Kun; Gou, Fujun; Zhu, Tongtong; Tan, Teng; et al.
Abstract: The deposition of niobium film on copper with excellent superconducting property at low-temperature conditions, used as superconducting radio frequency (SRF) cavity, is a serious and urgent technical problem to be solved at present. In this work, copper-based niobium (Nb) films with a thickness of 1.5–1.8 um, regulating the deposition temperature parameters and gas flow velocity in a tube furnace, were prepared by low-temperature chemical vapor depositing (CVD) method from the reaction between H2 and Niobium chloride (NbCl5 ) under pure Ar atmosphere. Fabricated Nb films were characterized by X-ray diffraction, scanning electron microscopy and energy dispersive spectroscopy, respectively. The results showed that the excellent crystalline quality and superconductive performance of Nb films were generated successfully by CVD at low temperatures of 650 °C–700 °C. The preparation process was optimized during deposition and the formation mechanism of Nb films was also discussed in detail. The magnetic moment versus temperature of the Nb sample prepared at 700 °C was also measured and the well-prepared Nb film deposited in the boundary layer region obtains the desired superconducting transition temperature of 9.1 K ± 0.1 K, almost equivalent to that of high pure Nb bulk material. The optimized CVD reaction method of Nb film with favorable morphology and expected superconductive property at low temperature provided a new strategy and technical process in designing the desired copper-based Nb film SRF cavity.